Thermal Neutron Capture Studies of Some Light Odd-Odd Nuclei - Ishaq, Abul Faiz Mohammed (My University, 1972)
Thermal neutron capture studies have been made of the odd-odd nuclei, 20F, 24Na, 28Al, 32P, 36Cl and 40K. The gamma ray spectra have been studied using a Ge(Li) pair spectrometer and revised decay schemes are presented for these nuclei. The Q-values and gamma ray multiplicities have been obtained for the reactions studied. The average partial widths for primary Ml and El transitions have been calculated for the six nuclei and compared with the theoretical estimates. The features of the capture gamma ray spectra are discussed and it is observed that for the six nuclei studied, the total intensity in the spectrum above the energy of 0.3 times the Q-value is nearly the same (~1.4 photons/capture).
Keywords: thermal, neutron, odd-odd, nuclei, gamma ray, spectra, capture